Monogenean infections in rabbitfish ( Siganus spp.) From the Cat Ba Archipelago Vietnam - Tran, Thi Binh; Nguyen, Thi Hoang Ha; Nguyen, Manh Hung; Tran, Thi Viet Thanh; Nguyen, Ha Van (Academia Journal of Biology, 2025)
A total of 133 white-spotted spinefoot (Siganus canaliculatus) and 80 mottled spinefoot (Siganus fuscescens) were examined between 2009 to 2025 to determine the prevalence, intensity, and species composition of monogenean parasites. Monogeneans were isolated, mounted by gelatin-glycerin, and stained with either carmin alum or trichome gomori for morphological identification. The infection rate in both fish species was high (> 75%), varying by sampling period (year). The mean intensity of infection in S. canaliculatus was 12.3 parasites per host (range: 1–100), which was higher than in S. fuscescens at 8.0 (range: 1–36). Six species of monogeneans were identified: Glyphidohaptor sigani Kritsky, Galli & Yang, 2007; Glyphidohaptor sp.1; Glyphidohaptor sp.2; Tetrancistrum indicum (Paperna, 1972) Kritsky, Galli & Yang, 2007; Tetrancistrum sigani Goto & Kikuchi, 1917 and Polylabris mamaevi Ogawa & Egusa, 1980. Five species were found in S. canaliculatus, five in S. fuscescens, and four species were shared between both hosts. These findings represent the first confirmed records of monogeneans in Vietnamese rabbitfish.A total of 133 white-spotted spinefoot (Siganus canaliculatus) and 80 mottled spinefoot (Siganus fuscescens) were examined between 2009 to 2025 to determine the prevalence, intensity, and species composition of monogenean parasites. Monogeneans were isolated, mounted by gelatin-glycerin, and stained with either carmin alum or trichome gomori for morphological identification. The infection rate in both fish species was high (> 75%), varying by sampling period (year). The mean intensity of infection in S. canaliculatus was 12.3 parasites per host (range: 1–100), which was higher than in S. fuscescens at 8.0 (range: 1–36). Six species of monogeneans were identified: Glyphidohaptor sigani Kritsky, Galli & Yang, 2007; Glyphidohaptor sp.1; Glyphidohaptor sp.2; Tetrancistrum indicum (Paperna, 1972) Kritsky, Galli & Yang, 2007; Tetrancistrum sigani Goto & Kikuchi, 1917 and Polylabris mamaevi Ogawa & Egusa, 1980. Five species were found in S. canaliculatus, five in S. fuscescens, and four species were shared between both hosts. These findings represent the first confirmed records of monogeneans in Vietnamese rabbitfish.